2009
DOI: 10.1137/080729657
|View full text |Cite
|
Sign up to set email alerts
|

On Perfect Matchings in Uniform Hypergraphs with Large Minimum Vertex Degree

Abstract: We study sufficient ℓ-degree (1 ≤ ℓ < k) conditions for the appearance of perfect and nearly perfect matchings in k-uniform hypergraphs. In particular, we obtain a minimum vertex degree condition (ℓ = 1) for 3-uniform hypergraphs, which is approximately tight, by showing that every 3-uniform hypergraph on n vertices with minimum vertex degree at least (5/9 + o(1))`n 2ć ontains a perfect matching.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
154
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(158 citation statements)
references
References 8 publications
3
154
0
1
Order By: Relevance
“…However, as pointed out in [3], the conditions on G in the case r = 3 and ℓ = 2 in Theorem 1.2 are not strong enough to guarantee this property. Consequently, the absorber construction from [12,22] fails. Moreover, this turns out to be the case for an arbitrary r and ℓ: Consider a graph G obtained by taking an r-partite complete graph with vertex classes V 1 , .…”
Section: Proof Strategymentioning
confidence: 99%
“…However, as pointed out in [3], the conditions on G in the case r = 3 and ℓ = 2 in Theorem 1.2 are not strong enough to guarantee this property. Consequently, the absorber construction from [12,22] fails. Moreover, this turns out to be the case for an arbitrary r and ℓ: Consider a graph G obtained by taking an r-partite complete graph with vertex classes V 1 , .…”
Section: Proof Strategymentioning
confidence: 99%
“…In this paper we consider vertex degrees in 3-graphs. Hàn, Person and Schacht [4] showed that m 1 (3, n) = 5 9 + o(1) n 2 .…”
Section: Introductionmentioning
confidence: 99%
“…We know that 4|U Following (7), we have 2 i=1 deg(u i ) + deg(v 1 ) < 3sn − 3η 1 n(n − 3η 1 n) + n/3 − 3. Since ε ≪ η 1 and n is sufficiently large, this contradicts (5).…”
Section: Proof Of Theoremmentioning
confidence: 92%